Utilizing Augmented Reality Technology in English Vocabulary - Emilia Emilia; Ismail Ismail; Hasan Hasan (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2025)
This study explores the potential of augmented reality (AR) technology in enhancing English vocabulary learning among EFL students at Muhammadiyah University of Enrekang. The study identifies key issues such as the lack of engagement and retention in vocabulary learning using traditional methods. A qualitative research approach was employed, involving 15 students and utilizing AR tools such as Google Expeditions, AR Flashcards, and Merge Cube to facilitate vocabulary learning. Data were collected through semi-structured interviews and classroom observations. The findings reveal that AR technology significantly enhances students' engagement, motivation, and vocabulary retention by providing interactive, multimodal learning experiences that place vocabulary in real-world contexts. However, several challenges were identified, including technical limitations such as device compatibility, internet connectivity issues, and the insufficient access to AR-capable devices. Additionally, concerns regarding the feasibility of scaling AR in resource-constrained settings, where students may lack access to adequate technological infrastructure, were raised. Furthermore, there is a critical need for comprehensive teacher training to effectively implement AR in the classroom. To address these challenges, the study recommends an integrated approach that combines AR technology with traditional teaching methods, alongside significant investment in technological infrastructure, development of affordable AR tools, and continuous professional development for teachers. This study contributes to the growing body of literature on the use of AR in language education and offers practical insights for overcoming the challenges of accessibility and scalability, ultimately improving the integration of AR in EFL classrooms, particularly in resource-limited contexts.